Between-Country Disparities in MDGs: The Asia and Pacific Region - Guanghua Wan; Yuan Zhang (Asian Development Bank (ADB), 2011)
This paper explores disparities in Millennium Development Goals among countries in the Asia and Pacific region, with a special emphasis on health Millennium Development Goals. It provides estimates on the extent of these disparities and depicts their trends. More importantly, sources or causes of the disparities are quantified and policy implications are discussed.
hdl:11540/1996
Keywords: 330; UN-Entwicklungsziele; Vergleich; Asiatisch-pazifischer Raum